Telaah Konteks Historis tentang Ayat Pelarangan Mendoakan Kerabat yang Musyrik: Studi Konsep Asbab Al-Nuzul Nasr Hamid Abu Zayd - Ulfah, Mailani; Zakiy, Ahmad (Lembaga Yasin AlSys, 2024)
Various restrictions on relationships or interactions with people of different beliefs sourced from the Qur’an lead to various responses, one of which is the attempt to find the reason behind the restrictions. QS. al-Taubah [9]:113 is one of the verses of the Qur’an that plays a role in creating these restrictions. This research aims to find various reasons behind the prohibition of praying for polytheists in QS. al-Taubah [9]:113 by looking at the dynamics of asbab al-nuzul of the verse and the socio-cultural reality of Arab society at that time which played a role in shaping the construction of the Qur’anic text by using Nasr Hamid Abu Zayd’s asbab al-nuzul approach. The type of research that will be used in this paper is library research. The results found from this study, first, the number of asbab al-nuzul narrations of this verse has implications, namely the assumption that QS. al-Taubah [9]:113 was revealed repeatedly, and other opinions that state such conclusions cause confusion so that there is a need for an in-depth study of hadith criticism. Secondly, the sharp conflict between Muslims and polytheists from the period of Makkah to Madinah influenced the construction of the text of QS. al-Taubah [9]:113 and the reason for the prohibition of praying and asking forgiveness for polytheist relatives. The nature of research that examines the historical aspects of a verse, needs to be appreciated and even enlivened in order to reveal the right interpretation of the Qur’an and find reasons from the aspect of tasyri’.